Welfare, Shocks, and Government Spending on Social Protection Programs in Lesotho - Boko, Joachim; Raju, Dhushyanth; Younger, Stephen D. (World Bank, Washington, DC, 2021)
This paper assesses the performance of government spending on social protection programs in reducing poverty and inequality in Lesotho, applying benefit incidence and microsimulation methods to 2017-2018 household survey data. The paper investigates the distributional effects of actual spending on social protection programs as well as those of a hypothetical alternative in which the spending is targeted through a proxy means test (PMT) formula used by the government for some programs. In addition, the paper explores the responsiveness of social protection programs to adverse shocks commonly reported by households in Lesotho, where recent natural shocks have had substantial economic effects.